Epidemiological survey of intentional and non- intentional poisoning cases in iraq during 2014-2016 - Wrood Salim Alkhfajy; Inam Sameh Arif; Munaf Hashim Zalzala (Journal of Global Pharma Technology, 2018)
Background:  Poisoning is a major global public health problem and one of the most common deaths in many societies. The goal of this study was to detect the percentage of patients with intentional and unintentional poisonings, and to define demographic factors, major toxic agents related to the occurrence of poisoning recorded by The Poisoning Consultation Center (PCC).Methods: This was a retrospective -epidemiological study covering data collected between 2014 and 2016 records of The Poisoning Consultation Center (PCC) / the Ghazi Hariri Specialized Surgery Hospital in the Baghdad medical city, Baghdad, Iraq.Results: Totally, 3213 cases associated with poisoning were evaluated. Among these cases, 3181 were reported as unintentional and only 32 cases as intentional poisoning. Females predominated among intentional cases (81%), and the majority of them belonged to the age group of 15-24 years. While, the 0-9-year age group was the most common among accidental cases. Metal poisonings, mostly copper, were found most frequently within accidental poisoning cases (74%). Carbamazepine ingestion was found to be the major toxic agent for committing suicides, followed by Paracetamol.Conclusion: Females had a greater propensity to commit intentional poisoning, and the housewives, the age group of 15–24 years and drug medications were more related with suicidal poisonings. A large scale of metal accidental poisoning are appearing in Iraqi cities where, bombing, military events, and waste incineration have led to increased public exposures. The results of this study may serve as evidence for new strategies in Iraq to prevent poisoning. Keywords: Accidental poisoning, Suicide, Epidemiology, retrospective analysis, public health.